Glycogen accumulation in adipocyte precursors from elderly and obese subjects triggers inflammation via SIRT1/6 signaling. Issue 8 (10th July 2022) - Terrón‐Puig, Margarida; Huber‐Ruano, Isabel; Sabadell‐Basallote, Joan; Ejarque, Miriam; Núñez‐Roa, Catalina; Maymó‐Masip, Elsa; Jorba, Rosa; Serena, Carolina; Vendrell, Joan; Fernández‐Veledo, Sonia
Abstract: Dysfunctional adipocyte precursors have emerged as key determinants for obesity‐ and aging‐related inflammation, but the mechanistic basis remains poorly understood. Here, we explored the dysfunctional adipose tissue of elderly and obese individuals focusing on the metabolic and inflammatory state of human adipose‐derived mesenchymal stromal cells (hASCs), and on sirtuins, which link metabolism and inflammation. Both obesity and aging impaired the differentiation potential of hASCs but had a different impact on their proliferative capacity. hASCs from elderly individuals (≥65 years) showed an upregulation of glycolysis‐related genes, which was accompanied by increased lactate secretion and glycogen storage, a phenotype that was exaggerated by obesity. Multiplex protein profiling revealed that the metabolic switch to glycogenesis was associated with a pro‐inflammatory secretome concomitant with a decrease in the protein expression of SIRT1 and SIRT6. siRNA‐mediated knockdown of SIRT1 and SIRT6 in hASCs from lean adults increased the expression of pro‐inflammatory and glycolysis‐related markers, and enforced glycogen deposition by overexpression of protein targeting to glycogen (PTG) led to a downregulation of SIRT1/6 protein levels, mimicking the inflammatory state of hASCs from elderly subjects. Overall, our data point to a glycogen‐SIRT1/6 signaling axis as a driver of age‐related inflammation in adipocyte precursors. Abstract : Glycogen deposition in adipocyte precursors as a driver of inflammation through a SIRT1/6‐dependent mechanism. Both aging and obesity impact the metabolic and inflammatory properties of adipocyte precursors. A novel pathway linking metabolic dysregulation and inflammation is shown.